Aligned Ion Conduction Pathway of Polyrotaxane-Based Electrolyte with Dispersed Hydrophobic Chains for Solid-State Lithium–Oxygen Batteries - Kim, Bitgaram; Sung, Myeong‑Chang; Lee, Gwang‑Hee; Hwang, Byoungjoon; Seo, Sojung; Seo, Ji‑Hun; Kim, Dong‑Wan (Nano-Micro Letters, 2024)
A critical challenge hindering the practical application of lithium–oxygen batteries (LOBs) is the inevitable problems associated with liquid electrolytes, such as evaporation and safety problems. Our study addresses these problems by proposing a modified polyrotaxane (mPR)-based solid polymer electrolyte (SPE) design that simultaneously mitigates solvent-related problems and improves conductivity. mPR-SPE exhibits high ion conductivity (2.8 × 10−3 S cm−1 at 25 °C) through aligned ion conduction pathways and provides electrode protection ability through hydrophobic chain dispersion. Integrating this mPR-SPE into solid-state LOBs resulted in stable potentials over 300 cycles. In situ Raman spectroscopy reveals the presence of an LiO2 intermediate alongside Li2O2 during oxygen reactions. Ex situ X-ray diffraction confirm the ability of the SPE to hinder the permeation of oxygen and moisture, as demonstrated by the air permeability tests. The present study suggests that maintaining a low residual solvent while achieving high ionic conductivity is crucial for restricting the sub-reactions of solid-state LOBs. Highlights: 1 Strategic materials design of polyrotaxane-based electrolytes was suggested by aligning the ion conduction pathways and dispersing hydrophobic chains for solid-state Li–O2 batteries. 2 Owing to intentional design, solid-state Li–O2 battery resulted in stable potential over 300 cycles at 25 °C.